Report of an extra-pair copulation in the Rufous Hornero, Furnarius rufus (Aves: Furnariidae) - Diniz, Pedro; Biagolini-Jr., Carlos (Papéis Avulsos de Zoologia, 2021)
In the last decade, studies in bird breeding biology have shown that infidelity is prevalent in socially monogamous species. Here, we describe an extra-pair copulation (EPC) event in the Rufous Hornero (Furnarius rufus), a socially monogamous bird with year-round territoriality and low levels of extra-pair paternity. Before the EPC, a within-pair copulation (WPC) occurred inside the pair’s territory. The WPC occurred on the ground and between a banded male (ca. 6 years-old) and an unbanded female. Ten minutes later this breeding pair invaded a neighboring territory, presumably to forage. The territorial male was chased back to its territory by an unbanded male neighbor after being detected. The male neighbor was paired with an unbanded female that did not participate in the aggressive interaction. When flying back to its territory the male neighbor copulated with the territorial female on the ground (ie. EPC). The territorial male flew, vocalized, and perched above the male neighbor, interrupting the EPC. The aggressive interaction then ceased as each pair resumed foraging in their respective territories. These observations suggest that Rufous Horneros can use EPC to obtain immediate benefits (food access in a neighbor’s territory). Moreover, WPC may be detected by neighbors and physical mate guarding and/or frequent WPC may be necessary to prevent EPC in the Rufous Hornero.